Exploring the reflective typology of novice EFL teachers in a Thai university - Thidaporn Jumpakate; Jeffrey Dawala Wilang; Corsica Kong (Institute of Advanced Engineering and Science, 2021)
This paper presents the reflective typology elicited from the three data sets of reflective writings written by novice teachers in Thailand's university context. As part of an action research study to improve a novice teacher’s professional development, two teachers volunteered to write reflections for a semester of their assigned courses. Three data sets of reflective writings were submitted at the end of a 16-week semester. Due to our desire to provide a more meaningful interpretation of the reflective writings, grounded theory was used, resulting in two emerging themes-descriptive code, which refers to the description of a specific event in the classroom, and reflective code, which include acts in the classroom where the teacher considered an option and reflected on it. In the typology derived from our study, reflections on teaching, students, and self are common among three data sets. Moreover, the instructional act is a common specific code in both descriptive and reflective codes. The typology can be used to investigate novice teachers’ reflective acts to further their professional development.